Factors Determining of Carbon Emissions Voluntary Disclosure in Indonesia’s Energy Sector Companies - HAPSARI, Dini Wahjoe; HARDIYANTI, Nadia Pramanik (PT Keberlanjutan Strategis Indonesia, 2024)
Reporting information on carbon emission from company operations is a form of social and environmental responsibility that contributes to the reduction of greenhouse gas emissions to achieve the SDGs target by 2030. This carbon-related reporting is the role of accountants through carbon accounting as a form of transparency and accountability, as well as an effort to reduce GHGs emissions produced by companies. This research is intended to see how energy sector companies implement voluntary disclosure of carbon emissions with several determinants which is reflected in the company size scale, the exposure carried out by companies in the company’s website media, and shareholding owned by institutions. The research population is in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022. Samples of this research used purposive sampling, so that 50 observational data were obtained consisting of 10 energy sector companies in 5 years period. Result show that media exposure influences carbon emission disclosure. Companies that present media exposure have an increase in the carbon emission disclosure level. Meanwhile, firm size and institutional ownership have no influence on the carbon emission disclosure. A company with a large size scale and high institutional shareholding does not guarantee that it will report information of carbon emission thoroughly.